Evaluation of a train-the-coach program in the context of a complex intervention for diabetes type 2 and coronary heart disease patients (P-SUP study) - Hamm, Isabel; Lehmann, Aliza; Gawlik, Angeli; Nacak, Yeliz; Timmke, Julia; Funke, Christian; Wilm, Stefan; Giesen, Lisa; Redaèlli, Marcus; Chermette, Chloé; Vitinius, Frank (Frontiers in Medicine, 2025)
IntroductionHealth coaching can address various health-related issues to improve health parameters and is used to manage chronic diseases, such as type 2 diabetes mellitus (T2DM) or coronary heart disease (CHD). For high-quality coaching, training as preparation is important. However, few training programs have been evaluated so far. In this study coaches should provide telehealth coaching to patients with T2DM and/or CHD within a peer support program to increase overall health status. In this paper the training for telehealth coaches was assessed with qualitative and quantitative methods.Materials and methodsThe training of the coaches (n = 4) consisted of 38 h with 11 units on health action process approach (HAPA), motivational interviewing (MI), nutrition and physical activity, the self-determination theory (SDT) and self-efficacy as well as practice coaching. The training was evaluated based on the Kirkpatrick model, quantitatively with an evaluation survey and a knowledge test on a 7-point Likert scale and qualitatively semi-structured interviews, with emphasis on the qualitative evaluation. A follow-up assessment 2.5 years after the training was conducted.ResultsIn the evaluation survey the overall training was rated as highly informative (M = 6.75) instructive (M = 6.5), practical (M = 6.25) and satisfactory (M = 6.25). The knowledge test was completed with 76 to 93% correct answers. The qualitative interviews revealed the usefulness of the MI and HAPA units. The practice coaching with actor patients as well as among each other were highlighted as important. Collectively, in-person training was favored by the participants compared to online training. The follow-up assessment emphasizes the results.DiscussionOverall, the evaluation showed the training was well accepted and perceived as useful in preparation for the coaching activity.